2017
DOI: 10.1016/j.entcom.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic difficulty adjustment on MOBA games

Abstract: This paper addresses the dynamic difficulty adjustment on MOBA games as a way to improve the players entertainment. Although MOBA is currently one of the most played genres around the world, it is known as a game that offer less autonomy, more challenges and consequently more frustration. Due to these characteristics, the use of a mechanism that performs the difficulty balance dynamically seems to be an interesting alternative to minimize and/or avoid that players experience such frustrations. In this sense, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Generally, difficulty adaptation is perceived as beneficial to one's gaming experience (Chen, 2007), as it leads to a more balanced gameplay. Recent work in the area of games user research has provided evidence that suggests that adaptive features in games also have a positive effect on the gaming experiences in shooting games (Bateman et al, 2011;Vicencio-Moreira et al, 2015), MOBA games (Silva et al, 2017), racing games (Cechanowicz et al, 2014), and casual games (Smeddinck et al, 2016): resulting in higher levels of enjoyment and fun (Newheiser, 2009), experiences of autonomy (Smeddinck et al, 2016;Klarkowski et al, 2016), and competence (Vicencio-Moreira et al, 2015). Though the effect of adaptive technologies on more generic player experiences, such as immersion and engagement, has not been explored to the same extent.…”
Section: Perception Of Adaptive Technology In Digital Gamesmentioning
confidence: 99%
“…Generally, difficulty adaptation is perceived as beneficial to one's gaming experience (Chen, 2007), as it leads to a more balanced gameplay. Recent work in the area of games user research has provided evidence that suggests that adaptive features in games also have a positive effect on the gaming experiences in shooting games (Bateman et al, 2011;Vicencio-Moreira et al, 2015), MOBA games (Silva et al, 2017), racing games (Cechanowicz et al, 2014), and casual games (Smeddinck et al, 2016): resulting in higher levels of enjoyment and fun (Newheiser, 2009), experiences of autonomy (Smeddinck et al, 2016;Klarkowski et al, 2016), and competence (Vicencio-Moreira et al, 2015). Though the effect of adaptive technologies on more generic player experiences, such as immersion and engagement, has not been explored to the same extent.…”
Section: Perception Of Adaptive Technology In Digital Gamesmentioning
confidence: 99%
“…Many studies propose automated game testing methods to replace manual testing. Several works [3][4][5] apply Petri-net based methodology that offers a graphical analysis for stepwise processes including choice, iteration, and concurrent execution. On the other hand, Dynamic Difficulty Adjustment (DDA) based on genetic algorithm [6] is proposed to heuristically search possible gameplay model and evaluate the overall leveling difficulty.…”
Section: Background: Game Development Life Cyclementioning
confidence: 99%
“…The simplest and most popular DDA methods are based only on performance measures (eg, in-game score), which provide an easily measurable and interpretable indicator of perceived game difficulty. However, although many studies have shown the positive effects of performance-based DDA on user experience [ 7 ], performance alone does not necessarily provide insight into the player’s psychological state, for example, a frustrated player can get a high score in a game without enjoying it. This has led to the development of affective games, an emerging type of videogame that adapts difficulty based on a combination of the player's performance and their psychological (cognitive and affective) state.…”
Section: Introductionmentioning
confidence: 99%